IMPROVING STUDENTS’ WRITING ABILITY IN NARRATIVE TEXT THROUGH PICTURE SERIES - Muryani Muryani (Universitas Madako Tolitoli, 2020)
The objective of the research is to prove whether the use of Picture Series is effective to improve students’ writing in narrative text. This pre-experimental study use 22 students’ as a sample. They are grade X1b of SMA Atmajaya Tolitoli. The procedure of this research consist of pre-test, treatment, and post-test. The researcher give pretest and posttest to know the use of Picture series can improve the students’ writing in narrative text or not. The result of the analysis show that Picture series contribute greatly to the students’ comprehension. It can be seen by the difference of the mean score between pre-test and post-test. The mean score of pre-test is 52.72 while in the post-test improved up to 75.81. The data of this research are analyze by SPSS Program 16.0. Moreover, the Minimum mastery Criterion of English lesson is 75 (seventy-five). Then the data of both tests are analyze by using T-test, and the result show that the T-test value 20.071 was high than T-table value 2.080. it can be inferred that Picture series is very effective to improve students writing ability in narrative text.Keywords: Improving, narrative text, picture series,teaching writing